2016
DOI: 10.1097/hcr.0000000000000142
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Outcomes in Cardiac Rehabilitation

Abstract: Despite recommendations in CR association guidelines to consider patient satisfaction, there is an absence of research assessing it. The studies that have assessed it administered tools of questionable psychometric rigor. It remains to be determined whether patient satisfaction is related to any meaningful outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Little is known about how to measure or improve patient satisfaction in CR or whether changes in programming can affect this perception. 93 In an era of increased focus on patient experience, this represents an important gap in both measurement and intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about how to measure or improve patient satisfaction in CR or whether changes in programming can affect this perception. 93 In an era of increased focus on patient experience, this represents an important gap in both measurement and intervention.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first study to our knowledge to have investigated patient satisfaction using the recommended generic and psychometrically validated measure in the CR setting 17. Results suggest that the PACIC23 is a reliable, valid, and sensitive measure of satisfaction for the CR setting.…”
Section: Discussionmentioning
confidence: 84%
“…Despite these recommendations, there is little evidence available regarding patient satisfaction with CR. A recent review identified only 8 studies in this area 17. The scant published data suggest that patients have high satisfaction, in particular with staff and the motivating environment, information received regarding disease, information on diagnosis and treatment, and self-management of medicine 18,19.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies also showed no significant difference in patient satisfaction attending in cardiac rehabilitation program. 15 , 19 So it is not clear that this questionnaire is enough much effective in cardiac rehabilitation settings.…”
Section: Discussionmentioning
confidence: 99%